Holographic scraping therapy for a patient with type 2 diabetes mellitus of damp-heat accumulating spleen syndrome and relayed nursing management (全息刮痧治疗1例湿热困脾型2型糖尿病患者的护理) - LI Jiao (李姣); HU Hairong (胡海荣); HUI Xinyuan (惠鑫源); LIU Sujuan (刘素娟) (中西医结合护理)
To observe the effect of holographic scraping therapy in treating one case of type 2 diabetes mellitus of damp-heat accumulating spleen syndrome, and to summarize related nursing measures. The Middle-Jiao area of side-forehead zone and 1/3 Middle-Jiao area of top-forehead zone were scraped with vertical scraping technique; The surface projection areas of abdominal pancreas and spleen body were scraped with side scraping technique; The corresponding projection area of spine, pancreas and spleen on the back were scraped with side scraping technique. In each conditioning cycle, 2 holographic acupoint areas and related meridian acupoints were scraped, twice per week, five times in a cycle. The holographic scraping therapy is effective to lower blood sugar and improve the quality of life in the patient with type 2 diabetes mellitus of damp-heat accumulating spleen syndrome. (观察全息刮痧治疗湿热困脾型2型糖尿病1例的效果, 总结护理经验。运用厉刮法刮拭头部额旁2带中焦区, 额顶带中1/3中焦区; 边刮法刮痧腹部胰脏、脾脏体表投影区; 边刮法刮拭背部脊椎胰脏、脾脏对应区。每次调理选择2个全息穴区加经络穴位刮拭, 2次/周, 5次为1个疗程。对湿热困脾型2型糖尿病患者实施全息刮痧疗法, 有助于降低患者血糖, 提高患者生活质量。)